Centro, centralidade e cidade média : o papel do comércio e serviços na reestruturação da cidade de Juazeiro do Norte/CE - Pereira, Cláudio Smalley Soares [UNESP] (2014)
The process of redefining the urban centrality of Brazilian mid-sized cities has been studied widely in the last decades. The present research seeks to contribute to the study of this theme, taking as an example of the city of Juazeiro do Norte, in the State of Ceará, considered a mid-sized city in the State owing to its functions on the scale of urban networks. For this research, different methodological proceedings were used, with an emphasis on interviews, questionnaires, fieldwork with photographic records, the survey of urban land use, and the interpretation of documentary material. Having the scale of a city as focus, the role of commerce and services in the production of urban space in Juazeiro do Norte has been analyzed to find out how the redefinition of centrality in the city through new locational rationales by economic agents has produced the ongoing restructuring of the city, how economic activities with regards to household appliances stores, bank services and large commercial centers, namely superstores and supermarkets linked to shopping centers or not, have exercised important functions in the displacement process of the tertiary sector away from the city center. On the other hand, the redefinition of centrality in the city of Juazeiro do Norte had been reflected in the social practices of the citizens...